Re- Rubbish Dalam Upaya Mewujudkan Konsep Green Village Di Desa Kasembon Kecamatan Bululawang, Kabupaten Malang - Wiraguna, Rayie Tariaranie; Nafi'ah, Nisbatun (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
Kasembon Village is one of the villages in Malang Regency which consists of Krajan I, Krajan II, Sukorejo, Meduran and Kaligoro hamlets. In Kasembon Village there is a plywood factory, namely PT Wijaya Cahaya Timber. From this description, the activities carried out by residents and production from factories will give rise to the potential for both organic and inorganic waste as well as plywood waste in quite large quantities. However, the rubbish and waste are only piled up in the yard and then burned, so it is feared that this could cause air pollution. To overcome this problem, Waste Bank outreach and waste and plywood waste processing skills training were held. The target of this activity is PKK women who are expected to be able to support the family economy by creating a creative industry from the use of waste banks in the future. This activity consists of socialization and discussion, demonstrations, and evaluation of activities by completing a posttest. Overall, this activity can be said to be successful with a participant satisfaction level of 60% and 36.7% very satisfied. Apart from that, 50% of the material presented was interesting and 43.3% was very interesting, thus providing usefulness with percentages of 56.7% and 43.3% being very useful. With this, if there were similar activities, the people of Kasembon Village would be willing to attend again with 53.3% willing and 43.3% very willing. Because apart from having a short-term impact, it turns out to have a long-term impact with 63.3% being able to be continued and 33.3% being able to continue after this activity is completed. The committee on duty was also greeted warmly because they showed a good attitude as much as 56.7% and very good 43.3%.